'Emergent reconstruction' in grounded theory: learning from team-based interview research. (February 2015) - Conlon, Catherine; Carney, Gemma; Timonen, Virpi; Scharf, Thomas
Constructivist grounded theory (CGT) methods render an interpretive portrayal, a construction of reality, strengthened when the process of construction is acknowledged. An Irish team study uses CGT to explore intergenerational solidarity at individual, familial and societal levels, and their interface. The study data comprise interviews with 100 people from diverse socio-economic and age groups. The article contributes insights on applying CGT in team-based interview research on a topic with such breadth of scope. This contrasts with the more usual focused inquiry with a defined population. Adapting the method's guidelines to the specific inquiry involved challenges in: framing the topic conceptually; situating research participants in contrasting social contexts to provide interpretive depth; and generating interview data with which to construct theory. We argue that interrogating the very premise of the inquiry allowed for emergent reconstruction, a goal at the heart of the method.